Mangrove forests in a rapidly changing world: Global change impacts and conservation opportunities along the Gulf of Mexico coast. (15th December 2018) - Osland, Michael J.; Feher, Laura C.; López-Portillo, Jorge; Day, Richard H.; Suman, Daniel O.; Guzmán Menéndez, José Manuel; Rivera-Monroy, Victor H.
Abstract: Mangrove forests are highly-productive intertidal wetlands that support many ecosystem goods and services. In addition to providing fish and wildlife habitat, mangrove forests improve water quality, provide seafood, reduce coastal erosion, supply forest products, support coastal food webs, minimize flooding impacts, and support high rates of carbon sequestration. Despite their tremendous societal value, mangrove forests are threatened by many aspects of global change. Here, we examine the effects of global change on mangrove forests along the Gulf of Mexico coast, which is a valuable region for advancing understanding of global change impacts because the region spans multiple ecologically-relevant abiotic gradients that are representative of other mangrove transition zones across the world. We consider the historical and anticipated future responses of mangrove forests to the following aspects of global change: temperature change, precipitation change, accelerated sea-level rise, tropical cyclone intensification, elevated atmospheric carbon dioxide, eutrophication, invasive non-native species, and land use change. For each global change factor, we provide an initial global perspective but focus primarily on the three countries that border the Gulf of Mexico: United States, Mexico, and Cuba. The interactive effects of global change can have large ecological consequences, and we provide examples that highlight their importance. While some interactions between global change drivers can lead to mangrove mortality and loss, others can lead to mangrove expansion at the expense of other ecosystems. Finally, we discuss strategies for using restoration and conservation to maximize the adaptive capacity of mangrove forests to global change. To ensure that the ecosystem goods and services provided by mangrove forests continue to be available for future generations, there is a pressing need to better protect, manage, and restore mangrove forests as well as the adjacent ecosystems that provide opportunities for adaptation in response to global change.